Muscular strength and its contribution to the accuracy of medium and long passes among youth handball players of Kiwan Club - Hussein, Emad Abbas; Ibrahim, Ahmed Jalal; Hussein, Mahmoud Abbas (Tanjungpura Journal of Coaching Research, 2026)
Background. Passing accuracy in handball depends on proper neuromuscular activation and fast muscle force production. There is still little evidence supporting which type of muscular strength has the greatest impact on youth players’ medium and long passes accuracy. Objectives. Investigate the correlation between muscular strength components and youth Kiwan club players’ medium and long passes accuracy and identify the contribution of each muscular strength component on each skill. Methods. The research design was descriptive correlational. Participants included youth players in Kiwan Handball club. Physiological variables consisted of three muscular strength components: explosive strength, speed-strength, and strength endurance. Skill-related variables included medium and long pass accuracy. Data were analyzed using descriptive statistics. Predictive strength of muscular strength components on medium and long passes accuracy was analyzed using multiple regression model, along with contribution analysis. Results. Muscular strength components were strongly correlated with passes accuracy. Regression analysis showed speed-strength is the only muscular strength component that significantly predicts youth players’ medium passes accuracy (t = 6.337, p